Rancang Bangun Sistem Kontrol Kecepatan Motor Fan AC 3 Phasa Dengan Panel Kontrol Variable Speed Drive pada sistem HVAC : Rancang Bangun Sistem Kontrol Kecepatan Motor Fan AC 3 Phasa Dengan Panel Kontrol Variable Speed Drive pada sistem HVAC - Nurhabibah Naibaho; Muslikun (Teknik Elektro Universtias Krisnadwipayana, 2024)
Regarding the importance of using fan motors in various industrial applications, such as ventilation systems and air conditioning systems. 3 Phase AC Fan Motor is one of the most frequently used components in HVAC systems because it has high reliability and efficiency in the use of electric power. However, in operation, a 3-phase AC fan motor requires speed control according to system requirements. Therefore, an appropriate and effective fan motor speed control system is needed. Variable Speed Drive VSD is an effective solution to control the speed of a 3-phase AC fan motor. Variable Speed Drive VSD is able to control the speed of the motor by adjusting the frequency given to the motor. In this research, a Variable Speed Drive VSD control panel will be designed and built to control the speed of a 3-phase AC fan motor. The test results were carried out after using the VSD control panel by setting the potentiometer for 6 conditions, namely when the frequency was set at 50 Hz, 45 Hz, 40 Hz, 35 Hz, 30 Hz, 25 Hz, the resulting rotation was 1449.5 RPM, 1347 RPM, 1206 RPM, 1059.2 RPM, 911.8 RPM, 764.4 RPM and the sound generated is 79.7 dB, 76.0 dB, 72.2 dB, 71.0 dB, 69.9 dB, 67.7 dB. By using the VSD control panel, the rotation of the 3-phase motor can be adjusted and adjusted according to the needs of the system, so that later it will have an impact on reducing sound levels and increasing user comfort.